Levo-Stepholidine as a Potential Cognitive Enhancer: Insights into Executive Function and Memory Improvements - Zhengwei Hu; Xueqing Zhu; Yirui Liang; Yuqiu Zhang; Ping Zheng; Xuehan Zhang (Biomedicines)
Background/Objectives: Levo-Stepholidine (l-SPD), a compound extracted from Chinese herbs, has the potential to treat psychotic disorders where cognitive deficits are a critical challenge. L-SPD displays a D1R agonism/D2R antagonism pharmacological profile, and its effect on cognitive function is still vague and lacks comprehensive study. Here, we investigated the impact of l-SPD on two core indexes of executive function, working memory and response inhibition, and learning and memory. Methods: Using a delayed alternation T-maze task (DAT), we investigated the impact of l-SPD on working memory, evaluated its effect on response inhibition using the stop-signal task (SST), and assessed the impact on learning and memory using trace fear conditioning in Sprague-Dawley rats. We further evaluated its effects on prefrontal glutamate receptor expression using western blot. Results: Rats receiving l-SPD made fewer errors in the T-maze, exhibited faster stop action in response to the stop signal, and showed longer-lasting memory retention. Molecular mechanism investigations reveal that l-SPD upregulates the expression of prefrontal glutamate receptors. These results demonstrate that l-SPD improves executive function and memory. Conclusions: Here, we show the enhancement effect of l-SPD on cognitive function, which provides essential implicants for the treatment of cognitive deficits, which is a critical unmet need in psychiatric care.